Effectiveness of corporate finance valuation methods: Piotroski score in an Ohlson model: the case of Mexico - Rocío Durán-Vázquez; Arturo Lorenzo-Valdés; Claudia Castillo-Ramírez (Journal of Economics, Finance and Administrative Science, 2014)
This study applied the Piotroski score for 63 selected companies of Mexico, for the period 2005 to 2011. The Piotroski score provides an evaluation on the historical financial performance of a company, with the evaluation of nine financial analysis ratios or criteria. We decided to add this score to the Ohlson Model (which was already tested in previous studies). It was found that the Piotroski score showed statistically significant results in the levels and differences variables. Asymmetric signs were also found in the Piotroski-score variables (levels and lagged), both of them are consistent according to the behavior of the Mexican market. The data were analyzed under a dynamic panel basis, with fixed effects, and the Sargan statistic for this analysis was fulfilled. – – En este estudio se aplicó la calificación de Piotroski a 63 empresas seleccionadas de México, para el período 2005 a 2011. La calificación de Piotroski proporciona una evaluación sobre el desempe\~no financiero histórico de una empresa, empleando nueve razones financieras. Decidimos a\~nadir esta calificación al modelo de Ohlson (ya probado en estudios previos). Se encontraron los siguientes resultados: la calificación de Piotroski es estadísticamente significativa en niveles y en diferencias. También encontramos signos contrarios en las variables de Piotroski (en niveles y rezagada), ambas coherentes de acuerdo al comportamiento del mercado mexicano. Analizamos los datos bajo la forma de panel dinámico con efectos fijos y el estadístico de Sargan, que para este análisis se cumplió.
Keywords: C33; D53; G11; 330; Financial markets; Piotroski score; Ohlson model; Dynamic panel of econometric estimation; Mercados financieros; Calificación de Piotroski; Modelo de Ohlson; Estimación econométrica de panel dinámico